PARTISIPASI PENDUDUK DALAM KONSERVASI DI SEGARA ANAKAN - Dede Sugandi (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2020)
The Sagara Anakan region is meeting some estuaries are undergoing a process of sedimentation. Impact of siltation and sedimentation caused the emergence of new deltas that lead to legal and institutional issues of ownership of the delta in the area. The mayor problemof this study is how the steps to perform the maintenance and protection, maintenance and protection efforts extent to support sustainable development and the factors that lead to sedimentation in the Segara Anakan?. The main purpose of this study is to learn the steps to perform the maintenance and protection, maintenance and protection of analyzing the efforts and analyze the factors that lead to sedimentation in th earea of Sagara Anakan. Conservation, vegetative, mechanical and chemistry methods that must be done. Segara Anakan area that to be studied is the area that has geographical location between 108001'15,66